Psoriasis: Epidemiology, clinical features, co-morbidities, and clinical scoring - Sunil Dogra; Rahul Mahajan (Wolters Kluwer Medknow Publications, 2016)
On the basis of current evidence derived from hospital-based studies, mostly from North India, the prevalence of psoriasis in adults varies from 0.44 to 2.8%, with a much lower prevalence in children. The peak age at onset in adults is in the third and fourth decade of life, with a slight male preponderance. It is recommended that population-based large epidemiologic studies should be undertaken in different parts of the country for estimating the correct prevalence of psoriasis in general population. Chronic plaque-type psoriasis is the most common morphologic presentation of psoriasis, accounting for more than 90% of all cases. Other morphologic variants that deserve special mention include palmoplantar psoriasis, pustular psoriasis, and recalcitrant psoriasis.For epidemiologic purposes, psoriasis can be classified into early and late onset psoriasis. Psoriasis can be classified on the basis of morphology and extent of involvement into localized and widespread disease.For the purpose of clinical trials, psoriasis may be classified as mild psoriasis, moderate psoriasis, and severe psoriasis. The literature shows that there is a significant risk of psoriatic arthritis (7-48%) in patients with plaque-type psoriasis. Hence, it is recommended to evaluate for its presence by detailed history taking and clinical examination, and if necessary, by appropriate radiological investigations. Evidence on the association between plaque-type psoriasis and cardiovascular disease risk factors and ischemic heart disease isinconsistent.On the basis ofavailable evidence, it is prudent to proactively look for metabolic syndrome, dyslipidemia, and obesity, especially in patientswith severe psoriasis (Level 1+ evidence based on systematic reviews and meta-analysis). Based on the current evidence, the psoriasis area severity index appears to be the most valid and reproducible clinical severity score in the management of adult patients with plaque-type psoriasis.